Helping Entrepreneurs Help Themselves: A Review and Relational Research Agenda on Entrepreneurial Support Organizations - Bergman, Brian J.; McMullen, Jeffery S. (Entrepreneurship Theory and Practice, 2022)
Entrepreneurial support organizations (ESOs), such as incubators and accelerators, are now ubiquitous. Despite this proliferation, their impact on entrepreneurs, ventures, and communities remains unclear, while academic research remains disjointed and largely descriptive, limiting understanding of the entrepreneurial support process and the influence of ESOs on it. Conducting a systematic review of 337 peer-reviewed articles involving five ESO forms—incubators, science parks, accelerators, maker spaces, and co-working spaces—we find that the literature’s conception of support is under-socialized such that there is a need for longitudinal, processual, and experimental examination of changes in the rich relationships between entrepreneurs and their ventures, entrepreneurs and other entrepreneurs, entrepreneurs and ESOs, and ESOs and external stakeholders. Conceiving of support as help to become self-sufficient, we offer an alternative, relational approach to research on entrepreneurial support and those organizations seeking to provide it.